The mutational nature of the contemporary Eurasian linguistic identity of the Russian-Kazakh border region - Koyshe, K. K.; Койше, К. К. (Tyumen State University, 2013)
The article deals with the processes of interpenetration of languages in the structure of modern Eurasian linguistic identity, reveals the nature of the interference, leading to the appearance of new features in the regional language of the Russian-Kazakh border areas. Russia’s border areas show the south of the Tyumen region, the Kazakh border region – North Kazakhstan. Russian population of the area consistently assimilated representatives of many people living in the study region (Khanty, Mansi, Komi, Kazakhs, Tatars, etc.), showing an example of a complex halfblood population Russian-dominated dominant. On the example of speech local Kazakhs and Russian authors show how the transformation in modern Eurasian linguistic identity of Russian-Kazakh border areas. В статье рассматриваются процессы взаимопроникновения языков в структуре современной евразийской языковой личности, выявляется характер интерференции, ведущей к появлению новых черт в региональном языке российско-казахстанского приграничья. Российское приграничье представлено югом Тюменской области, казахстанское приграничье – Северным Казахстаном. Русское население данной территории последовательно ассимилировало представителей многих народов, проживающих в исследуемом регионе (ханты, манси, коми, казахи, татары и др.), являя собой пример сложного метисного населения с преобладающей русской доминантой. На примере речи местных казахов и русских авторы показывают, каким образом происходит трансформация внутри современной евразийской языковой личности российско-казахстанского приграничья.